The Effectiveness of Benson Relaxation on Reducing Anxiety and Depression Levels in Patients with Chronic Illness: A Scoping Review - Abdul Mukid; Meira Erawati (Indonesian Journal of Global Health Research, 2025)
Anxiety and depression are commonly observed in populations with chronic physical illnesses. Treating symptoms of anxiety and depression in individuals with chronic physical illness can reduce psychological stress and improve overall physical health. One method to achieve a relaxation response is through the Relaxation Response Meditation Technique (RRMT) or Benson Relaxation. This study aims to determine the effectiveness of Benson Relaxation in reducing anxiety and depression levels in patients with chronic diseases. Literature sources were obtained through searches in PubMed, ScienceDirect, ProQuest, and SpringerLink databases, published between 2017-2024. The keywords used for the search included Benson Relaxation, Relaxation Response Meditation Technique (RRMT), Relaxation Response, Chronic Disease, Chronic Illness, Anxiety, and Depression. The articles obtained were then analyzed for differences and duplications. A diagram for visual representation of how the search and selection of articles were made is shown in the PRISMA-SR flow diagram. Data extraction was done by creating a table. Researchers identified seven articles. The interventions used were Benson Relaxation Technique and Benson Relaxation Therapy Combined with Spiritual Therapy to reduce anxiety and depression in patients diagnosed with multiple sclerosis, patients with heart failure, chronic kidney disease patients undergoing hemodialysis, elderly patients undergoing hemodialysis, hypertension, and elderly patients with kidney failure. Benson Relaxation has been proven effective in reducing anxiety and depression levels in patients with chronic illness.